Children with breakthrough varicella infection requiring hospitalization in Turkey (VARICOMP Study 2008–2013). Issue 32 (31st July 2015) - Dinleyici, Ener Cagri; Kurugol, Zafer; Kara, Ates; Tezer, Hasan; Tas, Mehmet Ali; Guler, Ekrem; Yasa, Olcay; Devrim, Ilker; Ciftci, Ergin; Ozdemir, Halil; Somer, Ayper; Ozen, Metehan; et al.
Abstract Introduction Varicella in previously immunized individuals, known as "breakthrough varicella". While the majority of breakthrough cases are mild, some may be severe, requiring hospitalization in previously healthy children or children with an underlying condition. Methods This report, as a part of the prospective national pediatric varicella hospitalizations study (including 29 centers, represent 50% of pediatric population) in Turkey, is aimed to evaluate breakthrough varicella infection requiring hospitalization before the routine use of single-dose live varicella vaccine in national program from 2008 to 2013 (<10% of the pediatric age group received a single-dose vaccine). Results In the time period, 1939 children were hospitalized due to varicella infection in Turkey; 36 children (20 boys, 16 girls, mean age 68.0 + 37.6 months, all received single dose live varicella vaccine) with breakthrough varicella infection. Breakthrough varicella infection might be severe in previously healthy children (61.1%) and children with immune-compromising conditions (38.9%). The time elapsed between vaccination and hospitalization was approximately 5 years, and neurological complications, mainly encephalitis and meningitis, were the most common reason for hospitalization in previously healthy children. Conclusion Pediatric breakthrough varicella requiring hospitalization have been seen in Turkey, is mainly observed in previously healthy children at 5 years after a single-dose varicella vaccine. The varicella vaccine has been implemented as part of the National Immunization Program in Turkey in 2013 (a single dose at age 12 months). Further surveillance in the same settings could evaluate the effectiveness of national immunization with single-dose varicella vaccine at 12 months of age and potential need for second dose of vaccine.